Hypocalcaemia, a possible manifestation of thyrotoxicosis. Issue 691 (May 1983) - Beigel, Y.; Arie, R.; Wysenbeek, A. J.; Halabe, E.; Blum, I.
Abstract : A severely thyrotoxic patient was found to have hypocalcaemia and tetany, which cleared when she became euthyroid. Cessation of treatment with propranolol and propylthiouracil resulted in a recurrence of the thyrotoxicosis and the reappearance of hypocalcaemia. Reinstitution of treatment resulted in a second remission of the thyrotoxicosis and correction of the hypocalcaemia. It is suggested that in this patient, the thyrotoxicosis was the cause of hypocalcaemia. The various pathogenetic mechanisms are discussed.